Translation and purification: Ayurvedic psychiatry, allopathic psychiatry, spirits and occult violence in Kerala, South India - Claudia Lang (Anthropology & Medicine, 2018)
In this paper, the author traces two parallel movements of institutionalized Ayurvedic psychiatry, an emergent field of specialization in Kerala, India: the ‘work of purification’ and the ‘work of translation’ that Latour has described as characteristic of the ‘modern constitution.’ The author delineates these processes in terms of the relationship of Ayurvedic psychiatry to (1) allopathic psychiatry, (2) bhutavidya, a branch of textual Ayurveda dealing with spirits, and (3) occult violence. The aim is to offer a model of these open and hidden processes and of Ayurvedic psychiatry’s positioning within a hierarchical mental health field characterized simultaneously by biopsychiatric hegemony and a persistent vernacular healing tradition. Through these processes, Ayurvedic psychiatry emerges as a relevant actor. It demarcates itself from both allopathic and vernacular epistemologies and ontologies while simultaneously drawing upon aspects of each, and, in this way, shows itself to be both deeply modern and highly pragmatic.